Personalized Cognitive Training in Unipolar and Bipolar Disorder: A Study of Cognitive Functioning - Preiss, Marek; Shatil, Evelyn; Cermakova, Radka; Cimermannova, Dominika; Flesher, Ilana (Frontiers in Human Neuroscience, 2013)
Patients with unipolar depressive disorder and in the depressive phase of bipolar disorder often manifest psychological distress and cognitive deficits, notably in Executive Control. We used computerized cognitive training in anattempt to reduce psychological affliction, improve everyday coping and cognitive function. We asked one group of patients (intervention group) to engage in cognitive training three times a week, for 20 minutes each time, for eight consecutive weeks. A second group of patients (control group) received standard care only. Before the onset of training we administered to all patients self-report questionnaires of mood, mental and psychological health, and everyday coping. We also assessed Executive Control using a broad computerized neurocognitive battery of tests which yielded, among others, scores in Working Memory, Shifting, Inhibition, Visuomotor Vigilance, Divided Attention, Memory Span and a Global Executive Function score. All questionnaires and tests were re-administered to the patients who adhered to the study at the end of training. When we compared the groups (between-group comparisons) on the amount of change that had taken place from baseline to post-training, we found improvements in Executive Control. Further exploration of the data showed that the cognitive improvements did not predict the improvements in everyday coping, and mood. Single-group data (within-group comparisons) show that patients in the intervention group were reporting fewer cognitive failures, fewer dysexecutive incidents and less difficulty in everyday coping. This group had also improved significantly on the six Executive Control tests and on the Global Executive Control score. By contrast, the control group improved only on the reports of cognitive failure and on working memory.